Kesalahan Pragmatik dalam Video Karya Mahasiswa pada Kuliah Kaiwa Chukyu Zenhan - Asrini, Dwi Puji (Chi'e: Journal of Japanese Learning and Teaching, 2021)
This research is a qualitative descriptive study to find out the pragmatic errors of student conversations in the video assignments of Kaiwa Chukyu Zenhan Course, and the factors that influence these errors. The object of this research is the conversations of students on the Kaiwa Chukyu Zenhan course assignments recorded on video. Research data collection was carried out by observing, taking notes, and recording methods to get an overview of the pragmatic errors in the video assignments of Kaiwa Chukyu Zenhan Course. The video, which contains student conversations on the theme of jikoshokai, is analyzed in order to get an overview of pragmatic errors and the factors that affect the pragmatic errors that occur.